2019
DOI: 10.1177/0886260519883869
|View full text |Cite
|
Sign up to set email alerts
|

The Trend of Interpersonal Violence Mortality at National and Provincial Levels in Iran From 1990 to 2015

Abstract: Interpersonal violence (IPV) is a major public health concern with a significant impact on physical and mental health. This study was designed to evaluate age–sex-specific IPV mortality trends and the assault mechanisms (firearm, sharp objects, and other means), at national and provincial levels, in Iran. We used the Iranian Death Registration System (DRS) and the population and housing censuses in this analysis. Spatio-temporal and Gaussian Process Regression methods were used to adjust for inconsistencies at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…3). An earlier study in Iran showed that the number of deaths due to attacks with rearms and sharp objects increased during the study period 1990-2015 (37). The results of a meta-analysis also showed that the trend of suicide attempt or SH is increasing in Iran (38).…”
Section: Discussionmentioning
confidence: 94%
“…3). An earlier study in Iran showed that the number of deaths due to attacks with rearms and sharp objects increased during the study period 1990-2015 (37). The results of a meta-analysis also showed that the trend of suicide attempt or SH is increasing in Iran (38).…”
Section: Discussionmentioning
confidence: 94%
“…Differences in the biological features of males and females are described as the reasons for this trend. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Violence is one of the five social harms [ 6 ] and associated injuries are the second most significant cause of mortality. While firearm use in violent situations has declined in Iran, the rate of deaths resulting from interpersonal violence among adults has increased between 1990 to 2015 [ 7 ]. About two-thirds of married women (67.3%) have experienced at least one type of domestic violence during their lifetime [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…About two-thirds of married women (67.3%) have experienced at least one type of domestic violence during their lifetime [ 8 ]. Soleimani et al 2021, estimated the prevalence of domestic violence during pregnancy in Iran to be 52% [ 9 ]. With the increasing elderly population, attention to issues related to elder abuse becomes important.…”
Section: Introductionmentioning
confidence: 99%